1993
DOI: 10.1007/bf01711088
|View full text |Cite
|
Sign up to set email alerts
|

Use of heat and moisture exchanging (HME) filters in mechanically ventilated ICU patients: Influence on airway flow-resistance

Abstract: The gas conditioning efficiency and design performance of the tested HMEs did not create a significant obstacle to airflow medium term mechanical ventilation; however, these devices should be cautiously used in patients with heavy bronchial secretions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
1
23
1
3
Order By: Relevance
“…Artificial noses have been reported to increase considerably the resistive load of the ventilator circuit in vitro [7]. However, an in vivo study suggests that artificial noses play a minor role in increasing airway resistance, but only in rare cases in which the filter membrane is exposed to particularly abundant secretions [8]. Lack of relevant mechanical interference was also confirmed by a study on patients with chronic obstructive pulmonary disease (COPD), in which the application of artificial noses was associated with no increase in dynamic pulmonary hyperinflation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial noses have been reported to increase considerably the resistive load of the ventilator circuit in vitro [7]. However, an in vivo study suggests that artificial noses play a minor role in increasing airway resistance, but only in rare cases in which the filter membrane is exposed to particularly abundant secretions [8]. Lack of relevant mechanical interference was also confirmed by a study on patients with chronic obstructive pulmonary disease (COPD), in which the application of artificial noses was associated with no increase in dynamic pulmonary hyperinflation [9].…”
Section: Introductionmentioning
confidence: 99%
“…The latter are frequently used because of their simplicity and lower cost [23,24]. Because HMEs are placed between the Y-piece and the patient, they add substantial deadspace to the circuit [25,26,27,28], and they can also marginally increase the resistance to flow [29,30]. It has been suggested in intubated patients that an increase of 5-10 cmH 2 O in the pressure support (PS) level is necessary to compensate the effects of the HME deadspace.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HMEs may increase resistance to flow [4,5]. Some studies [6,7,8,9] tion showed that the additional dead space of the HME induced an increase in minute ventilation to maintain efficient alveolar ventilation.…”
Section: Introductionmentioning
confidence: 99%